Localization strategies for global e-business - Singh, Nitish (Cambridge University Press, 2012)
"The acceleration of globalization and the growth of emerging economies present significant opportunities for business expansion. One of the quickest ways to achieve effective international expansion is by leveraging the web, which allows for technological connectivity of global markets and opportunities to compete on a global basis. To systematically engage and thrive in this networked global economy, professionals and students need a new skill set; one that can help them develop, manage, assess and optimize efforts to successfully launch websites for tapping global markets. This book provides a comprehensive, non-technical guide to leveraging website localization strategies for global e-commerce success. It contains a wealth of information and advice, including strategic insights into how international business needs to evolve and adapt in light of the rapid proliferation of the 'Global Internet Economy'. It also features step-by-step guidelines to developing, managing and optimizing international-multilingual websites and insights into cutting-edge web localization strategies"--